Barriers and strategies to successful tuberculosis treatment in a high-burden tuberculosis setting: a qualitative study from the patient's perspective - Ivan S. Pradipta; Lusiana R. Idrus; Ari Probandari; Bony W. Lestari; Ajeng Diantini; Jan-Willem C. Alffenaar; Eelko Hak (BMC, 2021)
Abstract Background Previously treated tuberculosis (TB) patients are a widely reported risk factor for multidrug-resistant tuberculosis. Identifying patients' problems during treatment is necessary to control TB, especially in a high-burden setting. We therefore explored barriers to successful TB treatment from the patients' perspective, aiming to identify potential patient-centred care strategies to improve TB treatment outcome in Indonesia. Methods A qualitative study was conducted in a province of Indonesia with high TB prevalence. Participants from various backgrounds (i.e., TB patients, physicians, nurses, pharmacists, TB activist, TB programmers at the district and primary care levels) were subject to in-depth interviews and focus group discussions (FGDs). All interviews and FGDs were transcribed verbatim from audio and visual recordings and the respective transcriptions were used for data analysis. Barriers were constructed by interpreting the codes' pattern and co-occurrence. The information's trustworthiness and credibility were established using information saturation, participant validation and triangulation approaches. Data were inductively analysed using the Atlas.ti 8.4 software and reported following the COREQ 32-items. Results We interviewed 63 of the 66 pre-defined participants and identified 15 barriers. The barriers were classified into three themes, i.e., socio-demography and economy; knowledge and perception and TB treatment. Since the barriers can be interrelated, we determined five main barriers across all barrier themes, i.e., lack of TB knowledge, stigmatisation, long distance to the health facility, adverse drug reaction and loss of household income. Conclusion The main treatment barriers can be considered to strengthen patient-centred care for TB patients in Indonesia. A multi-component approach including TB patients, healthcare providers, broad community and policy makers is required to improve TB treatment success.